Cryptocurrency price modelling - Seman, Juraj (2021)
The main purpose of the bachelor thesis is Bitcoin’s price modelling by using appropriate statistical approaches. The work is divided into a theoretical part and a practical part. Theoretical part deals with an introduction of the cryptocurrency as such and detailed description of the Bitcoin. Practical part focuses on characterization of the statistical approaches with subsequent application, in order to make our time series stationary and to find a suitable ARIMA model for Bitcoin’s price forecasting. On the basis of the tests performed, p-values, transformations and Akaike information criterion, we should be able to get a suitable ARIMA model for Bitcoin’s price forecasting.